The effect of cord blood drainage and oxytocin injection into the umbilical vein in the du ration of third stage of the labour (1994) - Sima Nazarpoor (Iran University of Medical Sciences, 1999)
A quasi experimental study was conducted in the labour rooms of one of the hospital's of the University of   Medical Science of Iran, to compare the effect ofcord blood drainage and oxytocin injection into the umblicat   vein in the duration of the third stage of labour.   A total of 180 women in the course of normal pregnancies with no complications and normal vaginal   dd ivery were selected randomly and divided in three groups. Each group consisted of 60 patients and were   designated as drainage, oxytocin and control group. All three groups received equally proper rou tine care in   the delivery room. Further, the second group after completion of the birth of the fetus had the cord blood   drained by the researcher and the third group also , aft er the completion of the birth ofthe fetus received   10 units of oxytocin diluted in /0 ml of normal saline through the umbhcal vein. All three groups were   matched and were similar, with the exception of placental weight, which was significantly lighter than the   other two.   Comparing the two intervention groups with control group the result showed that the drainage of the   placental blood from the cord has no effect on the duration of the third stage ofthe labour (t= 0.232).   Yet oxytocin injection into the umblical vein significantly reduced the duration of the third stage of the   labour (p< 0.005,t=3.824). In this study the two intervention groups were also compared: The results showed   that the oxytocin group had a shorter third stage of labour. It can be said thar the latter method is more   effective in facilitating placental ejection than cord blood drainge (p< 0.005,t=3.593).   It is recommended measures be provided for a smoother and shorter course of third slllge of labour.